(untitled) (Derna Academy Journal for Applied Sciences, 2025)
Background: Thyroid disorders are among the most common endocrine diseases in children, with hypothyroidism—both congenital and acquired—being the predominant type. However, most existing studies have been hospital-based, potentially overestimating prevalence and lacking generalizability to the community level. Aim: This study aimed to determine the prevalence and gender distribution of thyroid dysfunction among tested children and adolescents in Tobruk, Libya. Methods: A retrospective review was conducted on 234 pediatric cases who underwent thyroid function testing at medical centers in Tobruk. Data on age, gender, and thyroid hormone levels (TSH, FT3, and FT4) were analyzed to identify the frequency and pattern of thyroid dysfunctions. Descriptive statistics and correlation analyses were performed to assess relationships among variables. Results: The majority of the study population was euthyroid (97.9%), while only 2.1 % exhibited thyroid dysfunction. Five cases were identified with abnormal thyroid profiles—three with hyperthyroidism and two with primary hypothyroidism—without any recorded cases of subclinical or secondary hypothyroidism. Although thyroid disorders were slightly more frequent among females, the gender difference was not statistically significant. Weak positive correlations were observed between age and certain thyroid parameters, particularly among adolescents. Conclusion: The findings indicate a remarkably low prevalence of thyroid disorders among tested children and adolescents and that further community-based studies are required to determine true prevalence. contrasting with higher rates reported in hospital-based studies from other regions. The absence of significant gender differences and the predominance of euthyroid cases suggest that thyroid dysfunction is not a major public health concern in this setting. Nevertheless, targeted screening for high-risk groups—such as children with autoimmune conditions or developmental delays—remains essential. Future prospective research incorporating antibody testing and neonatal screening data is recommended to validate these findings and explore regional variations in thyroid health among Libyan children